Karasteristik Pemikiran Politik Ibn Khaldun - Hasaruddin Hasaruddin (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2010)
This article aims at outlining the characteristics of Ibn Khaldun’s political thought and at analyzing Ibn Khaldun’s views on state leadership. Based on Ibn Khaldun’s works, it clearly explains that Ibn Khaldun saw man from sociological and anthropological point of views. For him, human are not able to live without living and working with other creatures. This shows the necessity of organization for all mankind due to its function as an important factor in leading human existence to perfection.